2015
DOI: 10.3892/br.2015.516
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of telomerase in the nucleus pulposus tissues of degenerative lumbar discs

Abstract: Abstract. The pathogenesis of lumbar disc degeneration is extremely complex, and the expression and role of telomerase in degenerative lumbar disc tissues remains unclear. The aim of the present study was to detect telomerase expression in nucleus pulposus tissues of degenerative lumbar discs and to explore the correlation between telomerase expression and other factors typical of disc degeneration. A total of 8 patients with degenerative nucleus pulposus were included as the experimental group and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It also has been confirmed that telomerase activity is inhibited or destroyed in the degenerating intervertebral disc cells. Therefore, the cells cannot maintain chromosome balance, leading to continuous shortening of the telomere in the replication process and promoting cell senescence and intervertebral disc degeneration [ 94 - 96 ].…”
Section: The Cause and Effect Chain In Degenerative Disc Diseasementioning
confidence: 99%
“…It also has been confirmed that telomerase activity is inhibited or destroyed in the degenerating intervertebral disc cells. Therefore, the cells cannot maintain chromosome balance, leading to continuous shortening of the telomere in the replication process and promoting cell senescence and intervertebral disc degeneration [ 94 - 96 ].…”
Section: The Cause and Effect Chain In Degenerative Disc Diseasementioning
confidence: 99%
“…Telomere attrition is associated with this phenomenon; when the telomere is shortened, it results in senescence and ultimately apoptosis, which further deteriorates the condition of the cells and the IVD ( 8 ). Studies have indicated that diabetes accelerates telomere attrition in type 2 diabetic patients ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that telomere attrition and lower telomerase expression is involved in diverse types of diseases, including IVDD. Therefore, telomerase is considered a potential therapeutic target for these diseases ( 8 , 9 ). Telomerase reverse transcriptase (TERT), together with the telomerase RNA component (TERC), is the most important unit of the telomerase complex, though TERT is able to perform its function without the presence of TERC ( 11 ).…”
Section: Introductionmentioning
confidence: 99%